Job burnout on subjective wellbeing among clinicians in China: the mediating role of mental health - Fu, Yingjie; Huang, Derong; Zhang, Shuo; Wang, Jian (Frontiers in Psychology, 2023)
Background Although job burnout and mental health difficulties are prevalent negative influences on clinicians’ subjective wellbeing (SWB), there are few investigations into their relationships. This research investigates the mediating role of mental illness in the association between clinicians’ SWB and job burnout in China. Methods This study used the data collected from a cross-sectional survey conducted in China. Using convenience sampling, we conducted a face-to-face questionnaire survey among clinicians in a tertiary hospital in Shandong Province from August to September 2019. The 22-item Maslach Burnout Inventory-Human Service Survey (Chinese version) and the Personal Wellbeing Index-Adult assessed job burnout and SWB. The Chinese short version of Depression, Anxiety and Stress Scale (DASS-C21) assessed mental health. We also collected data on participants’ sociodemographic characteristics and job-related factors. Structural equation modeling (SEM) was applied to examine the associations between variables. Results Among the 422 participants, 80.8% of the participants reported at least one symptom of job burnout, whereas 5.7% reported all three symptoms of burnout. The prevalence rates of depression, anxiety, and stress were 40.3, 41.7, and 24.9%, respectively. Only 12.8% of the participants had high level of SWB. In mediation analysis, job burnout is positively associated with mental illness (β = 0.809, P < 0.001), mental illness had a significant negative association with SWB (β = −0.236, P = 0.013), and a negative association between job burnout and SWB was significant (β = −0.377, P = 0.002). Mental illness played a partially mediated role in the association between job burnout and SWB (indirect effect = −0.191, 95% CI: −0.361∼−0.017), and the mediating effect of mental illness can explain the 33.6% of the total effect of job burnout on SWB. Conclusion This study provides evidence that the effect of job burnout on SWB is partially mediated by mental illness among clinicians in China. Medical administration departments and hospital administrators should pay close attention to the job burnout and mental health of clinicians, so as to effectively improve the SWB of clinicians.